(untitled) (Global Journal of Computer Science and Technology, 2023)
As technological innovation rapidly grows in technology and education scholarship offices manage educational assistance that helps students continue their studies Most admin and scholarship officers of various scholarship programs use traditional ways of managing scholarship programs Traditional keeping records of documents and requirements can be misplaced and finding records is also a tedious job Therefore the researchers came up with making a web application for managing educational assistance which helps scholarship officers in collecting and managing information of scholars as well as for scholars to easily apply and submit requirements online